Penerapan Model Pembelajaran Group Investigation Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa - Handri Wijaya; Isop Sopiyah (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
This research was conducted because students' mathematical communication skills were still relatively low. This study aims to find out whether the increase in students' mathematical communication skills in the material Linear Absolute Value Inequality of One Variable who obtain mathematics learning with the Group Investigation learning model is better than students who receive conventional learning, as well as to determine students' attitudes towards learning mathematics with the Group Investigation learning model. The method used in this study was a quasi-experimental method using the Nonequivalent Pretest-Posttest Control Group Design. The population is all students of class X MIPA with a sample of class X MIPA 4 as the experimental class and X MIPA 3 as the control class. The experimental class was given treatment using the Group Investigation learning model, while the control class was given conventional learning treatment. The instruments used in this study were descriptive test instruments in the form of pretest-posttest, and non-test instruments in the form of questionnaires. Pretest-posttest data were processed using SPSS Statistics 17.0 Software for Windows. The average value of N-Gain on students' mathematical communication skills for the experimental class and control class is 0.57 and 0.23 with a significance of 0.00 ˂ 0.05, meaning that there are differences in the mathematical communication abilities of students who receive the Group Investigation learning model with students who get conventional learning. In addition, the results of obtaining a questionnaire with an overall average of 3.3 indicate a positive attitude towards the Group Investigation learning model. The results showed that there was an increase in the mathematical communication abilities of students who received the Group Investigation learning model better than students who received conventional learning. From the results of the questionnaire analysis of experimental class students showed a positive attitude towards the Group Investigation learning model